Prevotella copri, a potential indicator for high feed efficiency in western steers. (7th March 2019) - Brooke, Charles G.; Najafi, Negeen; Dykier, Katherine C.; Hess, Matthias
Abstract: There has been a great interest to identify a microbial marker that can be used to predict feed efficiency of beef cattle. Such a marker, specifically one that would allow an early identification of animals with high feed efficiency for future breeding efforts, would facilitate increasing the profitability of cattle operations and simultaneously render them more sustainable by reducing their methane footprint. The work presented here suggests that Prevotella copri might be an ideal microbial marker for identifying beef cattle with high feed efficiency early in their life span and in the production cycle. Developing more refined quantification techniques that allow correlation of P. copri to feed efficiency of beef cattle that can be applied by lay people in the field holds great promise to improve the economy of cattle operations while simultaneously reducing their environmental impact by mitigating methane production from enteric fermentation.